A crítica de Hegel e Agamben ao liberalismo político - Junior, Joel Decothé (Revista Ágora Filosófica, 2016)
Political liberalism receives strong criticism of two thinkers of very different periods of the history of philosophy: think here in Hegel and Agamben. In this paper the question that serves as a reference for the developed reflection is the critique of liberalism and its political stance that relies on contract as a guarantee of social consensus. Therefore, at first I wonder about the conception of state and political power in this criticism that Hegel initiates this political model. This implies the question of mediation between state power in universal terms and the strength of civil society in the field of particularity. On the theme of development, we seek to understand through reflection of Agamben via your vitalism its criticism of the political liberalism model. Agamben in this endeavor underscores the value of the category of life in its nakedness condition. It is also important to note that in the midst of this quandary, the Italian philosopher puts at stake the proposal for a policy that comes and the possibility of an ethic marked by the de-form-life as resistance to bio-political calculations tend to sacralization of the legal factor in liberal democratic architecture.